2022
DOI: 10.3390/rs14061417
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Learning Based Relay Selection for Underwater Acoustic Cooperative Networks

Abstract: In the complex and dynamically varying underwater acoustic (UWA) channel, cooperative communication can improve throughput for UWA sensor networks. In this paper, we design a reasonable relay selection strategy for efficient cooperation with reinforcement learning (RL), considering the characteristics of UWA channel variation and long transmission delay. The proposed scheme establishes effective state and reward expression to better reveal the relationship between RL and UWA environment. Meanwhile, simulated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The cooperative node is used to provide relay assistance to enhance the signal gain of receiving nodes and achieve reliable communication. Zhang et al proposed SA-FRL [35] to realize the cooperative communication of underwater networks based on Q-learning. SA-FRL selects cooperative nodes with good link quality and low access delay to improve the efficiency of cooperative communication.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooperative node is used to provide relay assistance to enhance the signal gain of receiving nodes and achieve reliable communication. Zhang et al proposed SA-FRL [35] to realize the cooperative communication of underwater networks based on Q-learning. SA-FRL selects cooperative nodes with good link quality and low access delay to improve the efficiency of cooperative communication.…”
Section: Related Workmentioning
confidence: 99%
“…The V-value of the not-selected candidate cooperative node nodes is not updated. With the iteration of training, the Vvalue will be continuously updated according to (34) and (35) and gradually converge, and a good cooperative communication policy will finally be highlighted. Figure 4 shows how the policy is generated based on the cooperative communication sub-algorithm.…”
Section: Cooperative Communication Sub-algorithmmentioning
confidence: 99%
“…It introduces a recovery mechanism to minimize the impact of routing voids on the data transmission performance. Zhang et al [27] introduced a reinforcement learning-based relay selection algorithm for UWSNs, combining RL with a simulated annealing algorithm to enhance the algorithm's performance. Ye et al [28] suggested a deep reinforcement learning-based medium access control protocol for underwater acoustic networks.…”
Section: Related Workmentioning
confidence: 99%
“…Utilizing average stochastic-inclination drop (SGD) strategy to prepare a repetitive organization, the backspread blunder signals will generally zero that suggests a restrictively lengthy intermingling time [35][36][37][38][39][40]. To handle this inclination disappearing issue, Hochreiter and Schmidhuber proposed long short-term memory (LSTM) in their trailblazer work of reference [26], which brought cell and entryway into the RNN structure.…”
Section: System Modelmentioning
confidence: 99%